Posterior instrumentation for osteoporotic fractures in the thoracic or lumbar spine: Cement-augmented pedicle screws vs hybrid constructs. Issue 4 (18th January 2023) - Chou, Po-Hsin; Lin, Hsi-Hsien; Yao, Yu-Cheng; Wang, Shih-Tien; Chang, Ming-Chau; Liu, Chien-Lin
Abstract : Background: Cement-augmented pedicle screws (CPS) and hybrid construct (HC), consisting of pedicle screws and additional hooks, are common fixation methods for osteoporotic spine fracture. No study has compared surgical results of CPS and HC for treating osteoporotic spine fracture. The aim of the study was to compare surgical results using CPS or HC for osteoporotic fractures of the thoracic or lumbar spine. Methods: This retrospective cohort study included 84 patients who received surgical treatment with CPS (n = 43) or HC (n = 41) for osteoporotic spine fractures from January 2011 to December 2015, with a mean follow-up of 67 months. Sixty-five patients with neurological deficits received long posterior instrumentation, short posterior decompression, and posterolateral fusion. The 19 patients without neurologic deficits received long posterior instrumentation without posterior decompression and fusion. Radiographic, clinical, and neurologic outcomes were evaluated. Results: The HC group had significantly shorter operative times (231 vs 258 minutes), greater blood loss (497 vs 427 mL), better immediate postoperative kyphosis reduction (10.6° vs 9.1°), and greater final reduction loss (9.8° vs 7.1°) than the CPS group. In both groups, significant loss of the kyphotic angle was apparent during follow-up. Improved ambulation after surgery occurred in 51.2% and 58.5% of patients in the CPS and HC groups, respectively. Neurologic function after surgery improved 0.5 and 0.7 grades in the CPS and HC groups, respectively. Implants failed in 2.3% and 2.4% of patients in the CPS and HC groups, respectively. The incidence of cement leakage from screw augmentation was 38.9%. Conclusion: The CPS and HC techniques for treating osteoporotic fractures of the thoracic or lumbar spine did not differ statistically in terms of improved radiologic and clinical outcomes, final neurologic and ambulatory function, or implant failure rates, making them equally comparable alternatives.